Michael Jordan : a team player - Petrucelli, Rita (Vero Beach, Florida : Rourke Enterprises, 1989)
Follows the life of the high-scoring Chicago Bulls player who could not get on his high school basketball team because he was too short. Includes advice on setting and reaching goals.
Keywords: Jordan Michael, 1963 -- Juvenile literature; Basketball players -- United States -- Biography -- Juvenile literature